Interleukin-8 heterozygous polymorphism (-251 T/A and +781 C/T) increases the risk of Helicobacter pylori-infection gastritis in children: a case control study - Dr Supriatmo; Gontar Alamsyah Siregar; Iqbal Pahlevi Adeputra Nasution; Oke Rina Ramayani (Medicinski glasnik, 2020)
Aim: To investigate the effects of interleukin-8 (IL-8)-251 T/A and +781 C/T polymorphism on the risk of Helicobacter pyloriinfection gastritis in children, and the IL-8 level of children with or without gastritis H. pylori infection according to polymorphism. Methods: This prospective, case control clinical study included 64 children 2-18 years old. A disease group (32 gastritis patients with H. pylori-infection) was compared with a control group (32 gastritis patients without H. pylori infection). Demographic characteristics of patients were taken by a questionnaire; gastritis was confirmed by gastroscopy, H. pylori infection was confirmed with rapid urease test. Serum IL-8 level was measured by ELISA, and IL-8-251 T/A and +781 C/T polymorphisms were analysed by RT-PCR. Demographic characteristics, IL-8 level, polymorphism of patients, and IL-8 level according to polymorphisms were compared between the groups. Results: Children with tobacco exposure were associated with an increased risk of H. pylori-infection gastritis by 3.4-fold. There was a higher IL-8 level in the disease group compared to the control group. The disease group with IL-8-251 AT polymorphism had a higher risk compared to TT polymorphism by 8.7-fold, and with IL-8 +781 CT polymorphism had a higher risk compared to CC polymorphism by 10.7-fold. Children in the disease group with IL-8-251 AT and TT, and +781 CT and CC polymorphisms produced a higher IL-8 level than the control group in respective polymorphisms. Conclusion: Children with H. pylori-infection gastritis have higher IL-8 production. There was an increased risk of developing H. pylori-infection in heterozygous-251 AT and +781 CT.
Keywords: chemokine CXCL8; genetic heterogeneity; genetic predisposition; gastrointestinal disease